Investigation on the ageing mechanism for a lithium-ion cell under accelerated tests: The case of primary frequency regulation service. (September 2021) - Leonardi, S.G.; Aloisio, D.; Brunaccini, G.; Stassi, A.; Ferraro, M.; Antonucci, V.; Sergi, F.
Highlights: Degradation of lithium-ion cell under a standard grid power profile. Accelerated ageing obtained by increasing ambient temperature. Investigation of ageing mechanisms by non-destructive analyses. Extrapolation of a thermal acceleration coefficient. Abstract: Lithium-ion batteries are increasingly used for the power network stabilization since renewable energy sources are massively exploited. Since the operating load profile has a strong impact on the degradation of lithium-ion cells, dedicated experimental tests can provide important information in this regard. Herein, a commercial high power 18, 650-type LiCoO2 -LiNiCoMnO2 /Graphite cell was aged according to a standardized endurance test from IEC 61, 427–2), which profile is formulated to simulate the primary frequency regulation service. In addition, accelerated ageing was obtained by increasing the ambient temperature to 45 °C. Then, a deep investigation was performed to assess the main degradation phenomena induced by the operating profile. For this purpose, incremental capacity (IC) and differential voltage (DV) analysis as well as electrochemical impedance spectroscopy (EIS) were performed at different state of health (SoH) of the cell. Moreover, in order to estimate the effects induced by the frequency regulation profile in comparison to the degradation phenomena caused by a typical full charge/discharge profile, an identical cell was also aged under this condition. Experimental evidences indicate that the operation under primary frequency regulation is less detrimental for the cell by capacity loss point of view, while larger internal impedance increase was observed in comparison to the typical full charge/discharge profile. Finally, a thermal acceleration coefficient was extrapolated to describe the cell capacity loss at room temperature under frequency regulation profile. Graphical abstract: Image, graphical abstract